If You Don't Believe in God, Do You at Least Believe in Aristotle? Evaluations of Religious Outgroup Members Hinge upon Moral Perceptions. Issue 2 (3rd April 2022) - Mallinas, Stephanie R.; Conway, Paul
ABSTRACT: Religious people tend to believe atheists are immoral. Although some work suggests that atheists themselves agree, such findings could also reflect symmetric ingroup bias in the moral domain, where atheists likewise view religious targets as untrustworthy and immoral. We examined how American religious and atheist participants rated the morality of atheist and religious targets and assessed a potential intervention: learning that targets adhere to a moral code. Across three studies, both religious and nonreligious participants demonstrated clear ingroup favoritism, rating ingroup targets more moral than outgroup targets. However, this ingroup bias was reduced when participants learned the target adheres to a warm and coherent moral system rooted in philosophy and concern for others. These findings extended beyond evaluations to downstream social consequences such as distancing. Such findings challenge arguments that atheists view themselves as immoral and point the way forward toward reducing religious ingroup bias.